Poultry health constraints in smallholder village poultry systems in Northern Ghana and Central Tanzania - Ouma, Emily Awuor; Kankya, Clovice; Dione, Michel; Kelly, Terra; Enahoro, Dolapo; Chiwanga, Gaspar; Abukari, Yakubu; Msoffe, Peter; Kayang, Boniface Baboreka; Zhou, Huaijun (Frontiers in Veterinary Science, 2023)
Smallholder poultry production is a major contributor to food security and rural livelihoods in lowand middle-income countries. However, infectious diseases limit improvements to smallholder poultry production and performance of the sector in general. Infectious diseases of poultry, especially viral diseases, have major impacts on the health and productivity of flocks and account for significant morbidities and mortalities of birds each year. This study utilized participatory epidemiology approaches to better understand the poultry health constraints and challenges faced by smallholder poultry producers in village poultry systems in Northern Ghana and Central Tanzania. The results show dominance of small scale semi-intensive and extensive scavenging poultry production systems in the study areas. Newcastle disease ranked as the highest cause of morbidity and mortality in chickens in the two countries. The disease occurred mainly during the months coinciding with the dry season in both countries. Other health challenges among poultry flocks included worm infestation, fowl pox, coryza and coccidiosis. Producers, especially in rural locations, had poor access to veterinary services and critical inputs necessary for poultry production. In the Northern region of Ghana, producers lacked definitive diagnoses for sick poultry due to a shortage of veterinary